APPLICATION OF ACCELERATED SHELF LIFE TEST (ASLT) METHOD FOR SHELF LIFE DETERMINATION OF PINEAPPLE HONEY JUICE: A SUSTAINABLE APPROACH TO ENHANCE FOOD SECURITY - Boni Mulia Putra; Adila Silmi Nuraini; Wahyu Qur’ani Nufus; Farhah Kamilatun Nuha; A.R Yelvia Sunarti (jses, 2025)
Abstract - Pineapple is a highly perishable horticultural commodity, generally consumed fresh and prone to spoilage within five days at room temperature. To reduce post-harvest losses and support sustainable food availability, processing into value-added products such as juice is required. Shelf life information is essential before commercialization to ensure product safety, quality, and consumer trust. This study determined the shelf life of pineapple juice using the Accelerated Shelf Life Test (ASLT) method. Pineapple juice was processed, packaged, and stored at chilling temperature (5 °C) and room temperature (30 °C). Sensory attributes, including color, taste, and aroma, were evaluated as critical parameters. The ASLT method accelerates quality changes under controlled conditions to estimate shelf life more efficiently. Results indicated that pineapple juice stored at 5 °C maintained acceptable quality for up to seven days, whereas storage at 30 °C significantly reduced shelf life. Findings highlight the importance of appropriate storage and processing in extending product shelf life, minimizing food waste, and supporting sustainable food security.